Pengaruh Sistem Manufaktur Berkelanjutan terhadap Daya Saing Perusahaan Industri di Indonesia - Nurmawaddah Pasaribu; Abdurrozaq Hasibuan; Ade Oka Syahputra; Jeany Amelia Putri (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This study uses a qualitative method to examine the influence of sustainable manufacturing systems on the competitiveness of industrial companies in Indonesia. In an increasingly competitive global market, implementing sustainability principles in manufacturing systems has become a vital strategy to enhance operational efficiency, reduce environmental impact, and strengthen a company’s image in the eyes of consumers and stakeholders. This research focuses on how industrial companies in Indonesia integrate economic, social, and environmental aspects into their production processes and how such integration contributes to long-term competitiveness. Data were collected through in-depth interviews with production managers, analysis of internal company documents, and direct observation of sustainable manufacturing practices. The findings reveal that companies consistently applying sustainable manufacturing systems are able to improve product quality, expand market share, and enhance customer loyalty. Additionally, they are more adaptive to environmental regulations and market trends demanding corporate social responsibility. Thus, sustainability becomes a strategic factor in enhancing industrial competitiveness in Indonesia.